Environmental performance evaluation of European farms by assessing polluting factors in joint production. (15th December 2021) - Pandey, Utsav; Singh, Sanjeet
Abstract: Measuring the environmental efficiency of firms using data envelopment analysis (DEA) has recently gained momentum due to the urgency of climate change. The existing literature on environmental efficiency ignores the internal structures of the production system and treats the production unit as a 'black box'. Thus, it fails to identify the exact source of inefficiencies, which complicates course correction in a multi-stage production system. In response to these inadequacies, this study takes into account the amount of pollutants emitted, in addition to the classic input and output parameters in DEA, in each of the stages to measure the environmental efficiency of the overall system and decompose it into stage-level environmental efficiencies. Two separate models assign each country two separate efficiency scores for its environmental and technical performance. To demonstrate the applicability of the proposed framework, the environmental performance of farms in the European Union is measured. The numbers of efficient farms in technical and environmental approaches are 21% and 8% of the total 130 farms, respectively. The average environmental efficiency scores of the two stages (crop production and animal husbandry) across the farms are found to sharply increase and decrease, respectively in comparison to their corresponding technical efficiency. The study also reveals some interesting conclusions. For example, the environmental performance improves for inefficient farms when they try to achieve technical competence. To achieve overall environmental efficiency, all the stages need to be fully efficient. Based on the shadow prices of the polluting inputs and outputs obtained from the two models, we calculate the marginal rate of substitution for the inputs and marginal rate of transformation for the outputs which help one in carrying out comparative analysis. For instance, the results indicate that fertilizer and forage land are responsible for the majority of the environmental inefficiency. Production of cereal and meat is economically efficient; whereas dairy farming is both resource-intensive and environmentally harmful. Based on this analysis, we suggest important policy measures at both the farm and the country levels.